Nano to micron-sized particle detection in patients' lungs and its pathological significance. Issue 5 (8th April 2019) - Forest, Valérie; Pourchez, Jérémie; Guibert, Cyril; Bitounis, Dimitrios; Leclerc, Lara; Sarry, Gwendoline; Vergnon, Jean-Michel
Abstract : Comprehensive mineralogical analyses (including nano to micron-sized particle detection) of patients' bronchoalveolar lavages allow obtaining new insights into the role of inhaled biopersistent particles in lung diseases. Abstract : Mineralogical analyses of clinical samples have been proven useful to identify a causal relationship between exposure to airborne particles and pulmonary diseases. However, this type of analysis only considers the micron-sized fraction of the particles, neglecting the specific impact of submicron/nano-sized particles which have been otherwise shown to be reactive and able to induce biological effects. To fill this gap, we previously developed an innovative protocol to isolate micron-sized particles from submicron/nano-sized particles contained in 100 bronchoalveolar lavage (BAL) and bronchial washing (BW) samples from patients who suffered from interstitial lung diseases (ILDs) (NanoPI, ClinicalTrials.gov Identifier: NCT02549248). We then determined qualitatively and quantitatively the metal load in each of these fractions. The aim of the present paper is to investigate correlations between these mineralogical analyses and clinical data. The mean concentration of submicron silica particles was found to be significantly higher in the BAL and BW samples from patients suffering from sarcoidosis than those from patients suffering from other ILDs (501 vs. 246 ng mL −1 for BAL and 564 vs. 292 ng mL −1 for BW, respectively). This finding suggests a potential role of submicron silica particles in the etiology of sarcoidosis and highlights the usefulness of comprehensive mineralogical analyses to obtain new insights into the role of inhaled biopersistent particles in lung diseases.